ICT usage to support agriculture transformation towards agribusiness among smallholder farmers / Mohd Shahrul Nizam Mohd Danuri - Mohd Danuri, Mohd Shahrul Nizam (Institute of Graduate Studies, UiTM, 2017)
The main objective of this research is to investigate and understand the factors that contribute to the usage of ICT to support the agribusiness transformation among smallholder farmers in Malaysia by extending the existing theoretical framework. The perception of smallholder farmers plays an important role in utilising ICT as tools for improving their agriculture and business activities. Agriculture provides the main and raw source of foods for humans. Agricultural activities have been developed intensely in modern techniques and activities depending on the country, culture, and environment, such as the global climate and sustainability. Malaysia still imports food, as local providers cannot support the supply and demand within the country. Hence, the government has introduced many initiatives to support the agricultural industry to produce more food for local needs. Instead of introducing agricultural programmes and educating farmers, the government is focusing on the use of agricultural technology with ICT-based tools, and farmers in Malaysia are gradually recognising the importance of tools, such as fertigation and precision agriculture; nevertheless, they are still unable to improve their yield and supply the local demand for food. The introduction of agribusiness to the farmers is still not well understood and it is difficult to implement due to their limitations as smallholder farmers. This research uses a multimethodology, to explore the nature of the phenomenon by integrating the multiple factor analysis with the integrated nature of the work, and an empirical system prototype has also been incorporated into the integrated information systems theory.